2023
DOI: 10.1155/2023/4206316
|View full text |Cite
|
Sign up to set email alerts
|

Induced Inflammatory and Oxidative Markers in Cerebral Microvasculature by Mentally Depressive Stress

Abstract: Background. Cerebrovascular disease (CVD) is recognized as the leading cause of permanent disability worldwide. Depressive disorders are associated with increased incidence of CVD. The goal of this study was to establish a chronic restraint stress (CRS) model for mice and examine the effect of stress on cerebrovascular inflammation and oxidative stress responses. Methods. A total of forty 6-week-old male C57BL/6J mice were randomly divided into the CRS and control groups. In the CRS group ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
(71 reference statements)
1
0
0
Order By: Relevance
“…49,50 Previous studies have shown that CRS triggers an increased oxidative stress response in various rat brain regions. [51][52][53] In accordance with this approach, the current data showed that rats exposed to CRS developed higher levels of reactive oxygen species (ROS) (TBARS) and lower levels of antioxidants in the brain (GSH). 34 The increased oxidative stress is likely related to the elevated glucocorticoid levels and increased glucose metabolism and oxygen consumption in response to stress, as well as the decreased antioxidant defense mechanisms in the brain that cause different generation of ROS.…”
Section: Papersupporting
confidence: 67%
“…49,50 Previous studies have shown that CRS triggers an increased oxidative stress response in various rat brain regions. [51][52][53] In accordance with this approach, the current data showed that rats exposed to CRS developed higher levels of reactive oxygen species (ROS) (TBARS) and lower levels of antioxidants in the brain (GSH). 34 The increased oxidative stress is likely related to the elevated glucocorticoid levels and increased glucose metabolism and oxygen consumption in response to stress, as well as the decreased antioxidant defense mechanisms in the brain that cause different generation of ROS.…”
Section: Papersupporting
confidence: 67%